Digitalisasi Birokrasi Melalui Pembangunan Smart ASN di Kantor Regional XII BKN Pekanbaru - Siti Khaeromah; Febri Yuliani; Hasim As’ari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This study aims to explain bureaucratic reform in the field of human resources at the Regional Office XII Pekanbaru. This research uses the descriptive qualitative method. Data were collected through interviews, observation, and documentation. Research informants include structural officials, the Bureaucratic Reform Team, the HR Management Structuring Working Group, and a number of related functional officials. The results of the study indicate that in the process of transforming the bureaucracy from manual to digital which runs at Regional Office XII BKN Pekanbaru, it is closely related to the development of human resources for the apparatus as one element in bureaucratic reform. The Smart ASN profile is formed through the development of the ASN management system that leads to the development of digital talent. The Smart ASN development strategy is carried out to overcome a number of problems that occur in the ASN management process.